Teaching Management by Management Exception - Chentnik, C.G.; Weatherford, P. A. (Academy of Management Journal, 1974)
In an evaluation of the personalized system of instruction (PSI), PSI-exposed students performed significantly better and retained more knowledge for extended periods than did students taught by a traditional lecture approach. These conclusions support other studies and indicate that schools of business should investigate PSI for use within their curricula.